Optimasi Proses Produksi Bioplastik Poli (3-Hidroksibutirat) Dengan Bakteri Bacillus sp FAAC 20801 Menggunakan Bahan Dasar Jerami Padi Setelah Fermentasi - Akmal Djamaan; Witra Aulia; Krisyanella Krisyanella (Jurnal Farmasi Higea, 2011)
The optimation of production process of  bioplastic poly (3 - hidroxybutirat) (P(3HB) fermentation by Bacillus sp FAAC 20801 bacteria, using straw as carbon source has been carried out. Detection of P(3HB) produced using gas chromatography. The highest glucosa level obtain by using H2SO4 5% for hidrolisis. From 46800 mg straw (glucosa concentration 200 mg/mL) produce 5379 mg biomassa and 0.058 mg P(3HB) ; from 83400 mg straw (glucosa concentration 400 mg/mL) produce 5011 mg biomassa and 0.124 mg P(3HB) ; from 142800 mg straw (glucosa concentration 600 mg/mL) produce 3992 mg biomassa and 2.309 mg P(3HB).